1999
DOI: 10.1016/s0893-133x(99)00103-7
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic System in Schizophrenia Reconsidered: Anticholinergic Modulation of Sleep and Symptom Profiles

Abstract: Receptors, Cholinergic; Receptors, muscarinic; Parasympathetic nervous system; Sleep, REM; Symptoms, positive; Symptoms, negative The dopamine (DA) hypothesis has dominated biochemical and pharmacological research on schizophrenia for about two decades. Although pharmacological data implicate increased DA activity in the pathogenesis of positive symptoms of schizophrenia, there is minimal association with negative symptoms (Crow 1980;Andreasen and Olsen 1982;Angrist et al. 1980). The poorly elucidated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 87 publications
(102 reference statements)
0
8
1
Order By: Relevance
“…One is that the appearance of AA is based on a hyperactivity of ACh proposed by Tandon et al [6,16], which is different from our hypothesis. According to their hypothesis, the appearance of AA is a compensation to ACh hyperactivity.…”
Section: Limitation Of the Anticholinergic Hypothesis Of Schizophreniacontrasting
confidence: 99%
See 3 more Smart Citations
“…One is that the appearance of AA is based on a hyperactivity of ACh proposed by Tandon et al [6,16], which is different from our hypothesis. According to their hypothesis, the appearance of AA is a compensation to ACh hyperactivity.…”
Section: Limitation Of the Anticholinergic Hypothesis Of Schizophreniacontrasting
confidence: 99%
“…These reports suggest that downregulation of ACh almost reaching the critical level activates the inflammatory system. The impairments of the cholinergic systems in schizophrenia after onset have been thoroughly investigated; some researchers indicated that cholinergic, especially muscarinic, systems play an important role in the pathogenesis of schizophrenia [15,16]. Postmortem studies have observed a decrease in the levels of muscarinic receptors in large areas of the brain in schizophrenia, and these findings have been well replicated [17,18].…”
Section: The Cholinergic System In Schizophrenia and The Anticholinermentioning
confidence: 99%
See 2 more Smart Citations
“…While several agents targeting these receptors are currently in various stages of study, alpha-7 nicotinic and M-1 muscarinic agonists and positive allosteric modulators are of greatest interest (Dineley et al, 2015; Felder et al, 2012). Whereas nicotinic agonists principally target cognitive symptoms (Rowe et al, 2015), muscarinic agonists appear to show promise in addressing positive symptoms (Tandon et al, 1999). Encenicline, an Alpha7 Nicotinic receptor agonist, which had shown promise in early phase trials, has not shown efficacy in phase 3 studies..…”
Section: Novel Therapeutic Targets and Emerging Treatment Strategiesmentioning
confidence: 99%